Gray and Green Revisited: A Multidisciplinary Perspective of Gardens, Gardening, and the Aging Process - Scott D. Wright; Amy Maida Wadsworth (Journal of Aging Research)
Over fourteen years ago, the concept of “gray and green” was first introduced by Wright and Lund (2000) to represent a new awareness and a call for increased scholarship at the intersection of environmental issues and the aging process. This review paper revisits that concept with a fresh perspective on the specific role of gardens and gardening in the aging experience. As example, gardening is one of the most popular home-based leisure activities in the US and represents an important activity in the lives of older adults in a variety of residential settings. Yet, there has been a lack of any comprehensive and multidisciplinary (science and humanities) examination of the nexus between gardening and the aging experience, and in particular with research connections to stewardship and caring. In this paper, we review contemporary articles demonstrating the multidisciplinarity of gardening and the aging process. First, we will focus on the beneficial psychological effects resulting from the cultivation of caring, including personal contentment and artistic expression. Second, we will focus on stewardship and how gardening increases health, community awareness, and a connection to future generations. On the surface, this may demonstrate a separation between the humanities and science, but we will clarify a symbiotic relationship between the two disciplines in our conclusion.